Distribution, speciation, and ecological risk assessment of heavy metals in surface sediments of Jiaozhou Bay, China. Issue 5 (3rd July 2016) - Lin, Yichen; Meng, Fanping; Du, Yongxiang; Tan, Yuhan
ABSTRACT: This paper analyzed the distribution and speciation of seven heavy metals in sediments in Jiaozhou Bay. The ecological risk was assessed using three index approaches (i.e., risk assessment code ( RAC ), contamination factor ( CF ), and potential ecological risk index ( PERI )) and by a comparison with sediment quality guidelines (Chinese Marine Sediment Quality Standards (CMSQS), and threshold effect level (TEL) and probable effect level (PEL) from the USEPA). Pb, Cr, As, Cu, Zn, and Hg contents at most sites were above the corresponding TEL and Class I criteria (CMSQS) value. Particularly, high contents of Cu, detected at sites S7 (124.5 mg kg −1 ) and S8 (118.3 mg kg −1 ), exceeded the respective PEL value, indicating that harmful biological effects might occur. Speciation analysis, individual CF, and RAC calculations suggested that Cd had the highest bioavailable fraction and thus posed a very high risk to aquatic ecosystem; Cu and Zn showed a medium–high risk. Both global CF and PERI analysis indicated a high pollution risk at sites S7, S1, S3, and S2, but the assessments of specific sites were different. The incomplete consistency suggested that it is necessary to consider both total contents and chemical speciation for providing a more realistic appraisal for the risk of heavy metals in sediments.